Extent and driving factors of innovation in Peninsular Malaysia furniture industry - Lim, Tau Wai (2015)
The furniture industry in Malaysia has shown tremendous growth rate due to the abundant forest resource, low-cost factor inputs and cheap workforce. However, the percentage share of gross domestic product (GDP) of manufacturing and agriculture sector has been narrowing in recent years. The Malaysian furniture industry’s Value Addition Intensity (VAI) is declining, due to the industry’s increased input costs. The ratio of innovation capacity analysis shows the negative trend which indicates the declining of successful innovation in the industry. Due to the current scarcity resources of the industry, innovation is very important to be taken into consideration in order to enhance the business growth and the economic performance in the nation. In this study, the main objective is to investigate the extent and driving factors of innovation in Peninsular Malaysia furniture industry. To be more specific, the study also aims to investigate the determinants factors of innovation, to identify the ranking of innovations sources and main problems of innovation faced by the industry. In this study also identify the awareness of industry towards National Timber Industry Policy (NATIP) which contain a specific thrust regarding to the innovation development of the industry. The result indicates the sample population of 98 surveyed companies by direct-interview agreed that the importance of innovation in the business,but their participation in innovation activities is limited. The sample population is mostly involved in Original Equipment Manufacturing (OEM) which referred to the company that originally built a given product, which was then sold to other companies to rebrand and resell. This has shows the limitation of innovation activity. Based on the theoretical framework applied to this study, which has adapted the theory of perceived attributes and types of innovation by The Organization for Economic Co-operation and Development (OECD), the companies perceived that there are five main factors, which has been extracted by factor analysis. The five major main driving factors of innovation are product development, organization structure and management, process trend, market growth and institutional support and quality, which are significantly important. The first factor is product development, which has includes raw materials supply, product use or application, design or functionality, raw materials price, and appearance. Market growth is the second factor consists of industrial relation, promotion activities, supporting industries, market demand, and market information. The third factor is organization structure and management which comprises of work culture, availability of skilled workers, and capable top management. The fourth factor is process trend which consists of production technology and quality system. Finally, institutional support and quality is the last factor which includes financial incentives, and training as well as education. The companies’ awareness towards the seven thrusts stated in National Timber Industry Policy (NATIP) is also relatively low. Based on the binary logistic model used in this study, there are only two variables were positively significant affecting their awareness towards NATIP, which are Marketing and Promotion, and Bumiputera Participation. This indicates the companies have positive awareness of relationship towards National Timber Industry Policy (NATIP), which is related to the thrust of Marketing and Promotion, and Bumiputera Participation. Thus, National Timber Industry Policy (NATIP) has to put more efforts on the other thrusts to enhance the effective policy implications in order to develop the industry, as well as increase the awareness of the companies in the industry.